2001
DOI: 10.1034/j.1600-0722.2001.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of experimental diabetes on mandible growth in rats

Abstract: The aim of the present work was to assess the effects of experimental diabetes on mandible growth in rats. Experimental diabetes was induced in rats, aged 26 d, by a single dose of 100 mg/kg b.w. of Streptozotocin (STZ). Thirty-one d post STZ or vehicle injection, the animals were killed. Mandibles were resected to determine Mandibular Skeletal Units dimensions (MSU) and overall mandible growth. Statistical analysis of results revealed, for STZ treated animals as compared to the control group: 1) a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 35 publications
1
36
0
1
Order By: Relevance
“…Mandibular length, height and length of the base were significantly lower in streptozotocin treated rats as compared with the control group. On the other hand no significant differences in the length of symphyseal process, alveolar length and height of the base were found in diabetic and control group [11]. El-Bialy et al [8] received similar results in clinical trials, investigating boys aged 14-16 years who had been diagnosed with juvenile diabetes at least 5 years before the study.…”
Section: Changes In the Craniofacial Bones Development In Type 1 Diabsupporting
confidence: 57%
See 2 more Smart Citations
“…Mandibular length, height and length of the base were significantly lower in streptozotocin treated rats as compared with the control group. On the other hand no significant differences in the length of symphyseal process, alveolar length and height of the base were found in diabetic and control group [11]. El-Bialy et al [8] received similar results in clinical trials, investigating boys aged 14-16 years who had been diagnosed with juvenile diabetes at least 5 years before the study.…”
Section: Changes In the Craniofacial Bones Development In Type 1 Diabsupporting
confidence: 57%
“…In the experimental research on rats with artificially induced diabetes with streptozotocin Giglio and Lama [11] showed a statistically significant reduction of mandibular growth in all dimensions compared with the control group, which in some individuals resulted in deformation of the mandible. The results showed a reduction in growth of symphyseal, coronoid, and alveolar heights, condyloid, angular, and base lengths, and condyloid width for diabetic animals.…”
Section: Changes In the Craniofacial Bones Development In Type 1 Diabmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory mechanisms responsible for normal morphogenesis of the face and head involve hormones, nutrients, mechanical forces, and various local growth factors. The poor growth and alterations in bone metabolism have been associated with T1DM in both humans and experimental animals (Giglio and Lama, 2001). It is of prime importance investigating the changes in craniofacial bone structure and dynamic bone formation in DM condition to explore the impact of the diabetic condition on various mandibular growth elements and bone quality.…”
Section: Outline Of Studying the Effect Of Diabetes Mellitus On Cranimentioning
confidence: 99%
“…Numerous experimental and clinical studies on the complications of diabetes mellitus have demonstrated extensive alterations in bone and mineral metabolism, linear growth, and body composition (Giglio and Lama, 2001). DM is a metabolic disorder characterized by disturbed glucose metabolism, manifesting primarily as chronic hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%